„Medea. Stimmen” Christy Wolf w kontekṡcie recepcji mitu w literaturze niemieckojęzycznej - Jabłkowska, Joanna (Collectanea Philologica, 2025)
This article examines the distinctive features of the German reception of antiquity. The first part highlights key aspects of this reception, particularly in the context of German Weimar Classicism and the Enlightenment. Subsequent sections explore the strong interest in mythology and antiquity in contemporary literature, especially in GDR literature, where mythological parables often served as a means to circumvent censorship. The main focus of the article is Christa Wolf’s novel Medea. Stimmen (1996). It demonstrates how Wolf reinterprets the Medea figure, discarding the traditional portrayal of her as a child murderer and instead depicting her as a victim of an inhumane, totalitarian system. This reinterpretation should not be read explicitly as a critique of the GDR or West German neoliberal capitalism, but rather as a broader, pessimistic vision of humanity – one that remains unwilling to renounce power struggles, xenophobia, and authoritarianism.